Dnmt3a protects active chromosome domains against cancer-associated hypomethylation - Raddatz, Günter; Bender, Sebastian; Lyko, Frank (PLoS Genetics, 2012)
Changes in genomic DNA methylation patterns are generally assumed to play an important role in the etiology of human cancers. The Dnmt3a enzyme is required for the establishment of normal methylation patterns, and mutations in Dnmt3a have been described in leukemias. Deletion of Dnmt3a in a K-ras-dependent mouse lung cancer model has been shown to promote tumor progression, which suggested that the enzyme might suppress tumor development by stabilizing DNA methylation patterns. We have used whole-genome bisulfite sequencing to comprehensively characterize the methylomes from Dnmt3a wildtype and Dnmt3a-deficient mouse lung tumors. Our results show that profound global methylation changes can occur in K-ras-induced lung cancer. Dnmt3a wild-type tumors were characterized by large hypomethylated domains that correspond to nuclear lamina-associated domains. In contrast, Dnmt3a-deficient tumors showed a uniformly hypomethylated genome. Further data analysis revealed that Dnmt3a is required for efficient maintenance methylation of active chromosome domains and that Dnmt3a-deficient tumors show moderate levels of gene deregulation in these domains. In summary, our results uncover conserved features of cancer methylomes and define the role of Dnmt3a in maintaining DNA methylation patterns in cancer., Dnmt3a is generally assumed to be a de novo DNA methyltransferase that plays an important role in establishing DNA methylation patterns during embryogenesis. However, mutations in the human DNMT3A gene have been detected in various cancers, suggesting that the enzyme might also be relevant for DNA methylation in adult tissues and in tumors. We have established genome-wide methylation profiles at single base pair resolution to define Dnmt3a-dependent methylation changes in a mouse tumor model. Our results show that mouse tumors with a functional Dnmt3a enzyme are characterized by regional hypomethylation, while Dnmt3a-deficient tumors showed a uniformly hypomethylated genome. Further data analysis revealed that Dnmt3a is required for maintaining normal DNA methylation patterns specifically in gene bodies and in active chromosome domains. Our study thus defines the role of Dnmt3a in maintaining DNA methylation patterns and provides a paradigm for understanding the effects of DNMT3A mutations on human cancer methylomes.